Letter from the bark Ohio - Ohio (Bark)
Anonymous letter (1863 December 27; South Atlantic) written from the bark Ohio of New Bedford, Mass., Daniel Flanders, master. The writer notes that whales were taken in the South Atlantic. Having learned that a Confederate raider, the screw sloop Alabama, was in the vicinity, the Ohio sailed to the Indian Ocean where it also fished for whales and later returned to the South Atlantic.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Flanders, Daniel; Confederate States of America. -- Navy; Alabama (Screw sloop); Whaling -- Atlantic Ocean; Whaling -- Indian Ocean; Whaling -- Massachusetts -- New Bedford; United States -- History -- Civil War, 1861-1865 -- Naval operations